Personality traits and social entrepreneurship dimensions In Peru and Argentina - Nga, Joyce Koe Hwee *; Priale, M. A.; Darmohraj, A.; Moschetti, M.; Fuchs, R. M.; Saenz, M. (2018)
This research aims to increase the comprehension of the influence of the Big 5 Personality Traits on social entrepreneurship dimensions (social vision, sustainability, social network, innovation and financial returns) in the context of Argentinian and Peruvian social enterprises. Previous research was often based on student samples and most of them do not integrate the Latin American landscape. This paper presents a unique sample of entrepreneurs operating in countries where social entrepreneurship has not been deeply investigated, but considered as potentially relevant to bridge the division between the State and the free market in providing sustainable resources for the social sector growth. Data from 109 Peruvian and Argentinian social entrepreneurs was collected via online questionnaires, and analyzed using a separate exploratory factor analysis for the dependent and independent constructs. Findings indicate Conscientiousness as the most influential personality trait in social entrepreneur’s dimensions, affecting all except for financial returns. Openness has significantly positive influence to social network and innovation, as Extroversion to social network and financial returns, with a significantly negative influence to sustainability. Finally, Neuroticism has significantly negative influence to social networks. Additionally, differences between Peruvian and Argentinian samples were found and could stem from cultural-economic context.